Juvenile Justice and Sharp Weapon Possession: A Socio-Legal Study in North Lampung - Abu Bakar; Sugeng Dwiono (BRIDGE : The Multidisciplinary Research Portal, 2025)
This study examined the dynamics of handling criminal cases involving juveniles carrying sharp weapons in North Lampung, Indonesia, using a qualitative socio-legal case study approach. The research aimed to analyze how formal legal norms are implemented in practice and how social and contextual factors influence law enforcement decisions involving children in conflict with the law. Primary data were collected through in-depth interviews with judicial actors, probation officers, and juveniles involved in sharp weapon possession cases, complemented by document analysis of relevant laws and court decisions. The findings indicate that although statutory provisions serve as the primary legal basis, their application is significantly shaped by judicial discretion, local social norms, and concerns regarding the long-term impact of punitive sanctions on juveniles. In rural and agrarian contexts, sharp weapons are often perceived as tools for daily use or self-protection, creating ambiguity between lawful and unlawful possession. This condition presents challenges for law enforcement and highlights the limitations of rigid punitive approaches. The study further demonstrates that rehabilitative and restorative justice-oriented responses, supported by inter-agency coordination and community engagement, are more consistent with the objectives of juvenile justice and child protection. This research contributes to socio-legal and juvenile justice scholarship by providing contextualized empirical insights from a rural setting and offers policy-relevant recommendations for developing more adaptive, humane, and sustainable legal responses to juvenile offending.